Relations between land-use and socio-economic structure on farms with and without agricultural land abandonment - Borec, Andreja (Annales. Series historia naturalis, 2005)
Agricultural land abandonment and forest expansion is becoming a serious problem in Slovenia. Spontaneous forest expansion has a negative effect on natural and social conditions. Thus the consideration of natural and social conditions is of high importance when talking measures to prevent forest expansion. In the article, the comparison of farms with and without abandonment of agricultural use regarding land-use and socio-economic characteristics was made. The result of test show no statistically significant differences at the 5 % level between farms with and those withoutabandonment of agricultural land regarding socio-economic structure. Analysis of variance ANOVA was used for estimating the difference between various socio-economic structures on farms with abondoned agricultural land. The results of ANOVA show a statistically significant differences (p<0.05) between socio-economic structures on the farms with abandonment of agricultural land. The ANOVA results pointed out that aged farms have the largest abandoned land areas. In order to ascertain the differences between farms with and without abandoned agricultural land regarding their land use structure, t-test was carried out, and its results have shown no statisticallysignificant differences between farms with and those without abandoned agricultural land regarding land-use structure.
Keywords: kmetije; natural environment; okolje; opuščanje kmetijske površine; raba tal